South Africa’s Financial Spillover Effects on Growth and Financial Development in the Southern African Development Community - Bara, Alex; Le Roux, Pierre (International Journal of Economics and Financial Issues, 2017)
The study assesses the spillover effects of shocks to South Africa’s financial sector on economic growth and financial development of other SADC countries. The study uses Generalised Impulse Response and Vector Decomposition of Bayesian VAR estimations applied on a panel data framework. The results indicate presence of positive, but weak, spillover effects on economic growth of other SADC countries, with the spillovers more pronounced in the credit market. Direct spillovers from financial sector in South Africa to financial sector of other SADC countries are also positive and relatively significant in the credit market than in the money market. Implicitly, the credit market can effectively transmit financial spillovers from South Africa into the region. Underdeveloped financial systems of other SADC countries, trade imbalances, strong real sector spillovers, and financial ‘spillbacks’, however, combine to constrain financial spillovers from South Africa. Keywords: Economic Growth, Financial Development, Financial Spillovers, SADC, South Africa JEL Classifications: R12, H13, R15, O16, G20